PENGARUH BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN AMDK MEREK AQUA (STUDI PADA MASYARAKAT DI KOTA BANDUNG) - Devi Krisnawati (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
This study examines the effect of brand awareness on purchase decisions Aqua brand of bottled water in the community in the city of Bandung. This study aimed to measure the level of brand awareness in the community Aqua in Bandung, analysis of consumer purchasing decisions Aqua, and the influence of brand awareness in this study using a top of mind dimension, brand recall, brand recognition, and consumption on consumer purchasing decisions Aqua. This type of research used in this study was a descriptive study using quantitative methods. The population in this study is a community in the city of Bandung with samples taken 100 respondents. Collecting data in this study using a questionnaire distributed to respondents using incidental sampling technique. These results indicate that the level of brand awareness is at its Aqua brand top of mind and included into the category of high and Aqua brand of bottled water purchasing decisions are in high positions. Based on a simple regression test results indicate the brand awareness influence on purchase decisions Aqua brand of bottled water by 70.1%. While based on the coefficient of determination variable brand awareness can influence purchasing decisions by 46.2%.